Feminimisme dan Gender Dalam Islam (Kajian ayat Quran yang berkaitan dengan feminisme dan gender) - Wahid, Iman Surya Maulana; Lubis, Nurainun; Zahra, Novia Fatimah; Luthfiyah, Zahra Nur; A, Ashari; Effendi, Rafni Aulia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to provide a comprehensive review of feminist theory and practice as well as gender studies in a contemporary context. Through an in-depth literature analysis, this study examines the historical development of feminism, various schools of feminist thought, and the contribution of gender studies in understanding the complexity of gender relations. The research also explores central issues in feminism and gender studies, including gender representation, gender-based violence, gender inequality across various spheres, and intersectionality. Research findings indicate that feminism and gender studies continue to evolve and provide an important framework for analyzing and addressing gender inequalities. This study emphasizes the importance of an inclusive and intersectional approach in understanding womens and mens experiences, as well as the need for collective action to achieve sustainable gender equality.